A Point-of-Use (POU) Water Disinfection: Silver Nanowire Decorated Glass Fiber Filters. (December 2020) - Bahcelioglu, Ecem; Doganay, Doga; Coskun, Sahin; Unalan, Husnu Emrah; Erguder, Tuba Hande
Graphical abstract: Highlights: Glass fiber filter (GF) was effectively coated with AgNW to produce a novel filter AgNW-GF filters achieved high disinfection performance with low Ag release AgNW-GF filters were found promising for point-of-use (POU) water disinfection Flow rate, AgNW loading and E.coli concentration affect the filter performance Abstract: Investigation of a new, low-cost, safe and highly efficient water disinfection alternative to conventional methods has prime importance. This study aims to develop silver nanowire decorated glass fiber (AgNW-GF) filters for the removal of E. coli from water. This is the first study to fabricate a novel AgNW-GF filter and to investigate its use for point-of-use (POU) water disinfection. To this purpose, the effects of flow rate, AgNW loading and influent E. coli concentration on the removal efficiency of E. coli and Ag release from AgNW-GF filters were investigated. Effect of filtrate volume on Ag release was also analyzed. Disk diffusion tests revealed that AgNW-GF filters with different AgNW loadings had antibacterial effects against E. coli at a concentration range of 10 3 – 10 8 CFU/ml. Flow tests were conducted in order to investigate optimal conditions at which AgNW-GF filters achieved the highest E. coli removal efficiency. Optimal flow rate, AgNW loading and influent E. coli concentration were found out as 1 ml/min, 9.9 mg/g, and 10 3 CFU/ml, respectively. The highest removal efficiency was obtained as 2.12 log after two-stage serial filtration under optimal conditions. The released Ag amounts were all below the limit value of 100 ppb for potable water. Under determined optimal conditions, AgNW-GF filter was found as a promising alternative for POU water disinfection method to be used in contaminated natural water (<10 3 CFU/ml).